A Tokyo Romance: A Memoir - Buruma, Ian (New York: Penguin Press, 2018)
A classic memoir of self-invention in a strange land : Ian Buruma's unflinching account of his amazing journey into the heart of Tokyo's underground culture as a young man in the 1970's When Ian Buruma arrived in Tokyo in 1975, Japan was little more than an idea in his mind, a fantasy of a distant land. A sensitive misfit in the world of his upper middleclass youth, what he longed for wasn't so much the exotic as the raw, unfiltered humanity he had experienced in Japanese theater performances and films, witnessed in Amsterdam and Paris. One particular theater troupe, directed by a poet of runaways, outsiders, and eccentrics, was especially alluring, more than a little frightening, and completely unforgettable. If Tokyo was anything like his plays, Buruma knew that he had to join the circus as soon as possible
Keywords: Authors, Dutch -- iography. -- 20th century; Theater -- Japan -- Tokyo